Faktor-faktor yang Mempengaruhi Keputusan Pembelian Skin Mobile Legends - Matthew Alfredo; Aria Ganna Henryanto (STEKOM PRESS, 2024)
The advancement of technology becomes important in entertainment industry without the exception of online games. One of the most popular games is Mobile Legends: bang Bang in which the number of players keeps on increasing annually. The purpose of this research is to evaluate skin purchase decision based on price perception, promotion, and product design in Mobile Legends: Bang Bang. Several independent variables that are used in this research include price(X1), promotion (X2), and product design (X3). This quantitative research is done with purposive sampling method through Google form questionnaires and is analyzed with SPSS program. There are 175 respondents who are from Surabaya that play Mobile Legends: Bang Bang. This research shows that all variables are valid and reliable, because the classical assumption test that is done proves there is no heteroscedasticity and multicolinearity as well as fulfill linearity and normality assumption. T-test that is done also shows that there is no significant effect of price perception on purchase decision eventhough showing positive correlation. While, promotion and product design prove significantly affect positive on purchase decision.